Pengaruh Aset Pajak Tangguhan, Beban Pajak Tangguhan, Dan Perencanaan Pajak Terhadap Praktik Manajemen Laba (Studi Kasus Perusahaan Consumer Non Cyclical Yang Terdaftar Di BEI 2019-2021 - Diana Wulansari; Cahyani Nuswandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the impact of tax planning, deferred tax asset, and deferred tax expenses on profits management. Consumer bon cyclical firms registered on BEI in 2019-2021 make up the study’s population. Sample selection using purposive sampling method and obtained 215 sample. The data collection method was carried out quantitatively and the data processing technique used multiple linier regression analysis. The data used is obtained from financial reported on the Indonesia Stock Exchange and can be downloaded via the website IDX and analyzed using SPSS. The test results show that deferred tax assets, and tax planning have a positive effect on earnings management. But the management profits in unaffected by the burden of deferred tax expenses. Keywords: deferred tax assets, deferred tax expense, tax planning, profits management